Urban green and blue infrastructure: A critical analysis of research on developing countries - Valente de Macedo, Laura Silvia; Barda Picavet, Marc Eric; Puppim de Oliveira, José Antonio; Shih, Wan-Yu (Journal of cleaner production, 2021)
This article reviews the current status of research on urban green and blue infrastructure (GBI) in developing countries. We critically analyzed a total of 283 papers addressing urban GBI in selected developing countries in Africa, Asia, Latin America and the Caribbean (LAC), published between 2015 and 2019. The review aimed to a) analyze publication trends and typologies of urban GBI; b) identify innovative problem-solving measures using urban GBI, and c) understand priorities, differences and similarities in the deployment of urban GBI between the regions. The article identifies a growing interest in the urban GBI concept in the Global South, with a focus on local sustainable development. Urban GBI aims to address issues of urban greenery, land use policies, food security and poverty alleviation. There is a large variation in the number of articles across regions, with Asia, and particularly China, as the subject having a much larger number of publications when compared to LAC and Africa. We found that the focus of research topics varied between regions, reflecting regional development needs, so that urban agriculture research predominated in Africa, and green spaces and parks in Asia and LAC. GBI is still not implemented as a low-impact development or innovative strategy, except in China, where researchers have examined several cases of systemic GBI use for addressing urban issues. More recently, studies began exploring the linkages between nature and cities in light of global environmental issues such as biodiversity loss and climate change. We conclude with recommendations to further examine empirical evidence of urban GBI deployment and its outcomes in the Global South, that could contribute toward conceptualizing natural resource management in a multi-scalar, multi-dimensional, and multidisciplinary framework. •Publications show that scientific interest in urban green and blue infrastructure (GBI) in the Global South is increasing.•Research on urban GBI varies according to specific regional needs.•Research on urban agriculture predominates in Africa, and on green spaces and parks in Asia, Latin America and the Caribbean.•Chinese cities are the subject of the largest number of publications showing a growing interest in the strategic use of GBI for addressing urban issues.•Further research is needed to gather more empirical evidence of urban GBI deployment and its outcomes in the Global South.